The Effectiveness of the Use of Short-Form Videos on the Learning Outcomes of Pancasila Education in Elementary Schools - Firmansyah, Arif; Herlina, Herlina; Muchdar, Muchdar; Muslim, Muslim; Mas'adi, Mas'adi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
Pancasila Education plays an important role in developing students' civic character and national values from the elementary school level. However, conventional teaching methods often make students less active and less able to understand abstract moral concepts. This study aimed to examine the effectiveness of short-duration videos in improving students' learning outcomes in Pancasila Education. This research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The study was conducted at SD Inpres Masigi, Parigi Moutong Regency. The research population consisted of third-grade students, while the sample involved two classes selected through purposive sampling and divided into an experimental group and a control group. The primary data were students' pre-test and post-test scores, supported by observation data, while secondary data were obtained from school documents, student records, and learning materials. Data were collected through tests, observation, and documentation. The data were analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, Independent Sample T-Test, and N-Gain analysis. The results showed that the data were normally distributed and homogeneous. The Independent Sample T-Test obtained a significance value of 0.007 < 0.05, indicating a significant difference between the experimental and control groups. The experimental group achieved a higher mean score than the control group, while the N-Gain score of 0.46 was categorized as moderate. Therefore, short-duration videos are reasonably effective as an alternative learning medium for improving elementary students' learning outcomes in Pancasila Education.